Islam, Jender dan Hukum Islam; Diskursus Kesetaraan Jender dalam Perspektif Hukum Islam - Hudan Mudaris (UIN Sunan Kalijaga Yogyakarta, 2015)
Among the global issues that could be on the agenda today is the issue of gender issues. This paper aims the increasingly widespread gender issues discussed on many occasions, so it is continuously rolling seminars both locally, and internationally. Gender differences, which led to injustice and even violence against women, essentially is a social and cultural construction that is formed through a long process. This paper starts from the discussion of sex and gender differences. Then the origin of the creation of women is an important issue to be discussed. Connected with the development of the popular study of womanhood with the term feminism, section of gender equality in Islamic law will examine issues around gender and women in the context of a growing, dynamic Islamic law. Allegedly religious texts are also factors that perpetuate injustice against women. Necessary so that the reinterpretation of religious texts do not merely confine women, but also gives equal portions and positions with men.